Respostas

2014-05-13T11:00:37-03:00
(a+x)²=(a+3+x).(a-2+x)
(a+x).(a+x)=(a+3+x).(a-2+x)
a²+ax+ax+x²=a²-2a+ax+3a-6+3x+ax-2x+x²
a²+x²+2ax-a²+2a-ax-3a+6-3x-ax+2x-x²
a²-a²+x²-x²+2ax-ax-ax+2a-3a-3x+2x+6
-a-x+6

Espero ter ajudado....
2014-05-13T11:10:23-03:00
A) (a+x)² = a² + 2ax + x²
b) (a+3+x).(a-2+x) = a
² -2a + x + 3a - 6 + 3x + ax - 2x + x² =
                           = a² -2a + 3a + x + 3x - 2x + ax + x² - 6 =
                           = a² + a + ax + 2x + x² - 6.
igualand a) e b) :
a² + 2ax + x² = a² + a + ax + 2x + x² - 6
a² - a² + 2ax - ax + x² - x² -a -6 = 0
ax - a - 6 = 0